KAJIAN SOSIALISASI KEBIJAKAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KELURAHAN SETIANAGARA, KECAMATAN CIBEUREUM, KOTA TASIKMALAYA, JAWA BARAT - Yudianto Permana; Trisna Noor Noor (Universitas Galuh, 2022)
Setianegara Village, Cibeureum District is one of the areas that has been designated as Sustainable Food Agricultural Land (LP2B) in Regional Regulation No.4 of 2012, socialization activities have been carried out by the local government, but the increase in land conversion is still happening. This study aims to determine how the socialization of sustainable food agricultural land policies in Setianagara Village, Cibeureum District, and to analyze the supporting and inhibiting factors for the realization of the socialization objectives. This research design is qualitative with interview and case study methods. The results of the analysis show that the socialization activities have been carried out from the city level to the sub-district level which was attended by farmers, who became the socializers, namely the Agricultural Service and the LP2B formulating team with the target group of farmers who own rice fields, with presentation methods and pamphlets, which are the objectives, namely as information LP2B land determination and agreement with farmers. The driving factor for the socialization activities was the lack of water availability for land needs, while the inhibiting factor for the achievement of the objectives of the socialization was inadequate implementation of the target group.